PENGARUH PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 3 BATUSANGKAR - Rospita, Adek (Departemen Matematika, 2024)
Learners are expected to have problem-solving skills in mathematics as one of the crucial things. However, in reality this ability is still low among school-aged individuals. Using the Creative Problem Solving (CPS) paradigm is a model to address this issue. The purpose of the study was to identify, evaluate, and characterize these abilities in class VIII of SMPN 3 Batusangkar whose learning used the CPS model more than the traditional model. The research design was a pseudo-experiment with a control group that only received a post-test. Students from SMPN 3 Batusangkar in grade eight became the population of this study. We used a basic random sampling strategy to collect the sample. The null hypothesis was rejected because the test data analysis resulted in a P-value = 0.00. This indicates that the eighth grade students at SMPN 3 Batusangkar who learned using CPS were superior to the conventional method in solving problems.